Analytical solution for geogrid-reinforced piled embankments under traffic loads. Issue 3 (17th June 2020) - Zhuang, Y.; Cheng, X.; Wang, K.
Abstract : This paper describes a simplified numerical model for geogrid-reinforced piled embankments considering dynamic loads. Based on this model, the vertical stress acting on the geogrid is investigated comprehensively and is found to exhibit an inverse trapezoidal distribution. An analytical solution for the geogrid-reinforced piled embankment under a static load is then derived for vertical equilibrium and an assumed inverse trapezoidal load distribution on the geogrid. This is extended by considering an additional vertical stress induced by the dynamic loads, based on the Boussinesq equation. However, the characteristics of the traffic loads (i.e. frequency and load numbers) are ignored. The analytical solution is then validated against three case studies and parametric numerical studies under various geometries (pile spacing and embankment height), geogrid stiffnesses and embankment friction angles. These parametric studies show that the geogrid tension increases with the pile spacing, embankment height and geogrid stiffness but decreases with the friction angle of the embankment. The pile spacing is found to be the most influential of all the factors examined in this paper, increasing from 2.0 m to 3.0 m when the geogrid tension is increased by approximately 248%.